Tunable thermal properties in yttrium silicates switched by anharmonicity of low-frequency phonons. Issue 4 (April 2018) - Luo, Yixiu; Sun, Luchao; Wang, Jiemin; Tian, Zhilin; Nian, Hongqiang; Wang, Jingyang
Abstract: Coordinated modulation of thermal resistance and thermal expansion compatibility has become a chief concern in designing reliable environmental/thermal barrier coating candidates for Si-based ceramics. This study reports phonon behaviors and thermal properties of prototypical silicates X2-Y2 SiO5 and γ-Y2 Si2 O7 . The nature of anharmonicity for low-frequency phonons is analyzed, and the finding is discussed with respect to specific crystal structures and interatomic force constants. Low lattice thermal conductivities ( κL ) basically derive from the giant phonon anharmonicity enhanced by interactions between low-frequency optic and acoustic phonons. γ-Y2 Si2 O7 is predicted with considerably lower thermal expansion coefficient ( αV ) than Y2 SiO5 . The mechanism is disclosed as an effect of the extensive number of low-frequency phonons with negative Grüneisen constants (contributing to negative thermal expansion) in γ-Y2 Si2 O7, together with its higher elastic stiffness against internal thermal pressure at elevated temperature. A guideline for simultaneously approaching low κL and low αV is proposed for searching promising E/TBC candidates.